Assessment of problem-based learning in dental education and exploring barriers to its implementation: theory to reality - Farrukh, Khadija; Ambreen Usmani; Syed Bilal Yousuf (Journal of the Pakistan Medical Association, 2023)
There are 59 dental colleges in Pakistan out of which 17 are in the public sector and 42 in private. However, only a few use problem-based learning methods, though it is a popular strategy in dental education all around the world. This study aims to assess problem-based learning model in dental education and explore the barriers of its implementation in a private dental college of Karachi. Qualitative case-study approach was employed. The philosophical stance used was critical realism. Qualitative data was collected by participant observation, video recorded observation and video elicited semi-structured in-depth interviews of five faculty members and 15 students. Results showed that students were more interested in interactive sessions while faculty members were in favour of problem-based learning sessions. Thematic analysis was done to generate themes. This research applies reproduction method to explain the necessary and contingent relations and causal powers. —Continue